Root cause ananlysis of cost overrun in interior projects - Avijit Halder (International Journal of Rural and Regional Development, 2024)
The construction industry is a path through which development of urban and rural India happens. The development of the project happens. The construction industry and its parties are associated with high degree of risk due to the nature of construction business activities, processes, environment and organization: Cost overrun is one of the most important problems in the construction one of the major problems faced by the construction industry is the cost overrun. The risk associated with the cost overrun for the stake holders are not defined which the root causes of the problems become. Therefore there is a need to study the root causes associated with the cost overrun and to solve the problem proactively to identify the real point of action to prevent the problem. Cost overrun is an unexpected increase in the money incurred in a construction project. Due to an underestimation of the actual cost of the project. The author has created a detailed analysis of the cause of cost overrun in Interior projects throughout the study of live case studies and arbitration and disputes. The Dissertation discusses in detail the causes of cost overrun in building projects .The thesis is a descriptive analysis of the causes of cost overrun in interior projects. Cost overrun is leading factor which affects the construction activities and it is more common in Fast track projects, the impacts of cost overruns are very high in developing countries fast track activities are much affected by cost overrun due to various factors throughout the project cycle. The deviations between the actual cost incurred during construction phase and primarily cost is known as cost overrun and it is one of the most predominant factors affecting the successful completion of the overall project, factors which are mostly influencing the cost overrun in interior fit-outs of mass construction projects and rank the factors identifies based on their impact mostly affecting the construction activities finally giving recommendations to overcome the critical factors
Keywords: Construction Projects; Cost Overrun; Environment; Interior Projects; construction